FSTL3 Induces Lipid Accumulation and Inflammatory Response in Macrophages and Associates With Atherosclerosis. Issue 6 (December 2019) - Runhua, Ma; Qiang, Ji; Yunqing, Shi; Wenjun, Ding; Chunsheng, Wang
Abstract : Abstract: FSTL3 as adipokine takes part in dyslipidemia and inflammatory response, but the association of FSTL3 with atherosclerosis is unclear. This study indicated that FSTL3 showed significantly higher level (control: 7.68 ± 3.10 vs. AS: 9.29 ± 2.37 ng/mL; P < 0.001) in atherosclerosis, and FSTL3 expressed higher in plaque of ApoE knockout mice and located in macrophages. Oxidized low-density lipoproteins induced expression and secretion of FSTL3, meanwhile FSTL3 promoted lipid accumulation in macrophages. The advanced study found that FSTL3 upregulated CD36 and LOX-1 expression in a dose-dependent manner; however, FSTL3 also evoked interleukin 1-β (IL1-β), monocyte chemoattractant protein 1 (MCP-1), tumor necrosis factor-α, and matrix metalloproteinase-9 (MMP-9) secretion in macrophages. On the contrary, that downregulated FSTL3 attenuated expression of oxidized low-density lipoproteins induced CD36, LOX-1, and inflammatory cytokines expressing. All of these results demonstrated that FSTL3 as a novelty cytokine takes part in the process of atherosclerosis through increasing lipid accumulation and inflammation through regulating CD36 and LOX-1 expression.